Relationship between results of treatment of patients with mandibular prognathism after orthognathic treatment and satisfaction with life - Bogusiak, Katarzyna; Puch, Aleksandra; Neskoromna-Jędrzejczak, Aneta (Journal of Stomatology, 2017)
Introduction. Prognathism is an occlusal-maxillofacial defect caused by excessive growth of the mandible in its anterior part in comparison to the size of the maxilla. Incorrect proportions of the face have a decisive impact on the deterioration of facial aesthetics, resulting in the fact that people with this defect are perceived by the society as less interesting and less attractive. Aim of the study. To assess the degree of patients’ satisfaction with the results of surgical treatment of prognathism, their appearance and satisfaction with life after orthognathic surgery. Material and method. The study included 53 people aged 17-51 years who agreed to participate in the survey. The study group consisted of 28 women and 25 men. Results. All patients were satisfied or very satisfied with the outcome of surgical treatment. Analyzing the responses to the questions in the survey it was found that women are more likely than men to perceive their facial appearance after the surgery as “good” or “very good”, and are less likely to evaluate it as “average”. Furthermore, it was shown that people who declared an increase in selfconfidence after surgery were also more satisfied with their own image. Greater increase in self-confidence was also associated with greater ease in making new relationships. Conclusions. Positive subjective assessment of the outcome of treatment affects the level of satisfaction with life of people after orthognathic surgery. The average value of life satisfaction in patients after surgery is higher than the average life satisfaction in a reference population of adults in Poland.